AAPM Task Group 264: The safe clinical implementation of MLC tracking in radiotherapy. Issue 5 (23rd March 2021) - Keall, Paul J.; Sawant, Amit; Berbeco, Ross I.; Booth, Jeremy T.; Cho, Byungchul; Cerviño, Laura I.; Cirino, Eileen; Dieterich, Sonja; Fast, Martin F.; Greer, Peter B.; Munck af Rosenschöld, Per; Parikh, Parag J.; et al.
Abstract : The era of real‐time radiotherapy is upon us. Robotic and gimbaled linac tracking are clinically established technologies with the clinical realization of couch tracking in development. Multileaf collimators (MLCs) are a standard equipment for most cancer radiotherapy systems, and therefore MLC tracking is a potentially widely available technology. MLC tracking has been the subject of theoretical and experimental research for decades and was first implemented for patient treatments in 2013. The AAPM Task Group 264 Safe Clinical Implementation of MLC Tracking in Radiotherapy Report was charged to proactively provide the broader radiation oncology community with (a) clinical implementation guidelines including hardware, software, and clinical indications for use, (b) commissioning and quality assurance recommendations based on early user experience, as well as guidelines on Failure Mode and Effects Analysis, and (c) a discussion of potential future developments. The deliverables from this report include: an explanation of MLC tracking and its historical development; terms and definitions relevant to MLC tracking; the clinical benefit of, clinical experience with and clinical implementation guidelines for MLC tracking; quality assurance guidelines, including example quality assurance worksheets; a clinical decision pathway, future outlook and overall recommendations. Abstract :